INTEGRATING THE TEACHING OF CULTURE BASED READING AND ESSAY WRITING TO BUILD STUDENTS CULTURAL AWARENESS - Deddy Sofyan; Istiqlaliah Nurul Hidayati; Asih Wahyuni (Pedagonal : Jurnal Ilmiah Pendidikan, 2017)
The title of the research is integrating the teaching of culture based reading and essay writing to build students cultural awareness. Two main aims were conveyed in the research. First, it was aimed at supporting students to write an essay based on what they had read (to give them background knowledge and to build their reading habit) and the second was building students cultural awareness and helping them realize that their nation actually has fabulous local wisdoms. By realizing that the nation has deeply meaningful local wisdoms, they will love and protect the nation with their body and soul. The researchers integrated this teaching of local wisdoms by asking the students to firstly read a cultural based text and discussed what they understand about the text with their friends. The text contained a description about different cultures in several countries. The titles of the texts were for example: Maintaining Eye Contact in Some Cultures, Innocent Gestures that Mean Rude Abroad, The Ethics of Gift Giving all over the World, etc. After being read, the text was then discussed in the classroom. The students gave their opinion as well as their experience related to the topic. The last activity was writing an essay with the same topic yet the culture being discussed in the writing had to be about the students own culture. The method that was employed in the research was mixed method. The qualitative data was gained from classroom observation and the portfolio of students writings while the quantitative data was gained from questionnaires distributed to the students. The results were first the students found out how to write an essay and second, they realized that their culture has high values to be appreciated. Thus the love to the nation was well established.Key Words: Reading-Writing Integration, Cultural Awareness, Essay Writing.